2022
DOI: 10.3390/fermentation8090458
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Influence of Microbial Fermentation on the Nutritional Value of Soybean Meal

Abstract: The aim of this article is to increase the nutritional value of soybean meal while reducing the content of antinutrients by microbial fermentation of soybean meal with a mixed culture of probiotic microorganisms (Bacillus subtilis, Aspergillus niger, Saccharomyces cerevisiae, Lactiplantibacillus plantarum) at two different hydromodules. The addition of microorganisms increased the content of easily digestible protein and amine nitrogen in fermented soybean meal (30:110 and 30:130, hydromodulus soybean meal:wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
4
6
0
Order By: Relevance
“…The results, which showed an increase in protein content of 2.97 to 6.96% supported this hypothesis and correlate with the findings of Sukhikh et al (2022) and Sharawy et al (2016) who found an increase in protein content with fermentation time as the result of activities of a consortium of microorganism. These results also provide evidence that fermentation by a consortium of microorganisms is more efficient than by isolated strains (Sukhikh et al, 2022). However, this result disagrees with the report of Wang & Hesseltine (1981), Ene-Obong & Obizoba (1996) and Onweluzo & Nwabugwu (2009) who stated that the fermentation process did not significantly change the total protein content and amino acid composition of substrates.…”
Section: Proximate Analysissupporting
confidence: 89%
See 3 more Smart Citations
“…The results, which showed an increase in protein content of 2.97 to 6.96% supported this hypothesis and correlate with the findings of Sukhikh et al (2022) and Sharawy et al (2016) who found an increase in protein content with fermentation time as the result of activities of a consortium of microorganism. These results also provide evidence that fermentation by a consortium of microorganisms is more efficient than by isolated strains (Sukhikh et al, 2022). However, this result disagrees with the report of Wang & Hesseltine (1981), Ene-Obong & Obizoba (1996) and Onweluzo & Nwabugwu (2009) who stated that the fermentation process did not significantly change the total protein content and amino acid composition of substrates.…”
Section: Proximate Analysissupporting
confidence: 89%
“…During fermentation, microorganisms hydrolyze proteins and it complexes to release free amino acids, which can be used for the synthesis of new proteins (Frazier & Westhoff, 1978). Because of the microorganism's rapid growth in its own biomass, it was hypothesised that it contributed to an increase in protein content (Sukhikh et al, 2022). The results, which showed an increase in protein content of 2.97 to 6.96% supported this hypothesis and correlate with the findings of Sukhikh et al (2022) and Sharawy et al (2016) who found an increase in protein content with fermentation time as the result of activities of a consortium of microorganism.…”
Section: Proximate Analysissupporting
confidence: 56%
See 2 more Smart Citations
“…This finding is in partial agreement with the results of Sukhikh et al . (2022), in which the fermented soybean meal had stronger free radical scavenging ability than soybean meal. These findings supported the fact that fermented soybean meal has good antioxidant activity, which can be used in the development of functional food and nutritional health products.…”
Section: Biological Activities Of Fermented Soybean Mealmentioning
confidence: 99%